As relações da urbanização e da dengue em Primavera do Leste, Mato Grosso - Mendes, Simone de Oliveira (2017)
By having as transmitter the Aedes aegypti mosquito, dengue has become a concern and a serious problem for the population and consequently to public health authorities. It is already known that the disease is directly related to the proliferation and the index of the infestation of the vector, it is in turn dependent on environmental factors that Luke or condition its multiplication. In this sense, the purpose of this study was to understand the causes of the expressive increase in dengue fever in the urban area of the municipality of Primavera do Leste - MT in the period from 2011 to 2015. For this it was analyzed the growth of spring urban area and the characterisation of the sanitation infrastructure that each neighbourhood has both employing geoprocessing resources and on-site surveys. On the other hand, it also analyzed the time-spatial variation of the mosquito infestation indices and the notifications of the city's dengue fever cases obtained at the municipal secretariat for epidemiological surveillance which were aggregated at the level of neighbourhoods and months, seeking Investigating the hypothesis that such an expressive increase in the disease in this period could be related, above all, with socio-environmental conditions found in the eastern spring districts. The main results showed that the municipality of Primavera do Leste experienced a seven-fold increase in the number of notifications, from 174 reported cases of dengue in 2011 to 1350 in 2015, which made it one of the eight municipalities with the highest number of dengue notification in the state in 2015. During the period of the study, the year of 2013 presented greater amounts of notifications of the Epidemiological Surveillance, 1462 notifications, with a land index in a greater number of months with risk of disease outbreak , with values above 4% in that year. It was observed a territorial expansion of dengue of the central districts of the urban area to the peripheral districts, during the period of the study. It was also verified that even in the districts that presented high incidence of the disease there is good infrastructure of environmental sanitation such as asphalt, garbage collection, among others. However, also a large quantity of garbage was observed in vacant lots and sidewalks, conditions favorable to the proliferation of vector in the urban environment. Finally, it is possible to affirm that the identification of the neighborhoods that present the highest incidence of the disease, as well as the socioenvironmental conditions of those places that can influence the proliferation of the vector, contribute to the health actions to combat the disease, according to the needs of each local.